2022
DOI: 10.3233/hab-210450
|View full text |Cite
|
Sign up to set email alerts
|

Blood microbiota composition in Iranian pre-diabetic and type 2 diabetic patients1

Abstract: BACKGROUND: Type 2 diabetes as the most prevalent metabolic disorder, is one of the major causes of morbidity and mortality worldwide. Recent studies suggest that body microbiota may play a role in developing metabolic disorders including type 2 diabetes. The objective of the present study was to investigate the blood microbiota composition in Iranian pre-diabetic and type 2 diabetic patients compared to healthy individuals. METHODS: Blood samples were taken after 12-h fasting from 90 participants, 30 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Six of thirty-one studies focused on the T2D comprising of 4992 individuals. Out of six studies, four studies have a randomized controlled population [ 47 , 49 , 51 , 59 ] while one study has no controls [ 50 ]. Five studies used different variable regions and sequencing methods using the rRNA while Amar et al used rDNA [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of thirty-one studies focused on the T2D comprising of 4992 individuals. Out of six studies, four studies have a randomized controlled population [ 47 , 49 , 51 , 59 ] while one study has no controls [ 50 ]. Five studies used different variable regions and sequencing methods using the rRNA while Amar et al used rDNA [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 46 ] which may increase one’s risk. Pre-diabetic and patients with morbid obesity tend to show lower abundance of Akkermansia , and Faecalibacterium ( Table 2 ) compared to healthy individuals [ 49 ]. However, Bacteroides was found in abundance in people who were statistically less likely to develop T2D [ 47 ], suggesting that Bacteroides may act as a buffer against the development of T2D.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of visceral tissues previously considered sterile, it has been repeatedly shown that they contain microbial genetic material ( Aagaard et al, 2014 ; Ghaemi et al., 2021 ; Sookoian and Pirola, 2021 ). Indeed, hereby we could detect these from healthy arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pre-diabetes or type 2 diabetes have fewer Faecalibacterium , Akkermansia , and Bifidobacterium bacteria in their leukocytes than healthy people, according to an epidemiological study on Iranian diabetes patients. The bacterial loads of E. coli and Bacteroides fragilis were higher in pre-diabetic individuals than healthy individuals, while type 2 diabetes groups had higher Lactobacillus , E. coli , and Bacteroides fragilis ( Ghaemi et al., 2021 ). However, according to a case study in the Chinese population, no differences were reported in the baseline microbiota diversity of diabetes and control participants.…”
Section: Healthy Blood Bacteria Dysbiosis In Chronic Diseasesmentioning
confidence: 97%